1886 Ga. Laws 17 - (:unkn) unknown (My University, 1886)
Ch. 54: Imposed $100 occupational tax on dealers of pistols, revolvers, dirks, Bowie knives, and "pistol or revolver cartridges."
Keywords: TAX - DEALERS